Respuestas
Respuesta dada por:
1
X = radicando de la raíz cubica.
![( \sqrt[3]{x})^{3}=-3 \\ \\ (x^{ \frac{1}{3}})^{3}=-3 \\ \\ x^{ \frac{3}{3}}=-3 \\ \\ \boxed{x=-3} ( \sqrt[3]{x})^{3}=-3 \\ \\ (x^{ \frac{1}{3}})^{3}=-3 \\ \\ x^{ \frac{3}{3}}=-3 \\ \\ \boxed{x=-3}](https://tex.z-dn.net/?f=%28+%5Csqrt%5B3%5D%7Bx%7D%29%5E%7B3%7D%3D-3+%5C%5C++%5C%5C+%28x%5E%7B+%5Cfrac%7B1%7D%7B3%7D%7D%29%5E%7B3%7D%3D-3+%5C%5C++%5C%5C+x%5E%7B+%5Cfrac%7B3%7D%7B3%7D%7D%3D-3+%5C%5C++%5C%5C++%5Cboxed%7Bx%3D-3%7D)
Por tanto la raíz cubica de -3 elevada a la 3 da de resultado -3.
Por tanto la raíz cubica de -3 elevada a la 3 da de resultado -3.
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años